The Modulation by Anesthetics and Analgesics of Respiratory Rhythm in the Nervous System - Hao, Xuechao; Yang, Yaoxin; Liu, Jin; Zhang, Donghang; Ou, Mengchan; Ke, Bowen; Zhu, Tao; Zhou, Cheng (Current Neuropharmacology, 2024)
Rhythmic eupneic breathing in mammals depends on the coordinated activities of the neural system that sends cranial and spinal motor outputs to respiratory muscles. These outputs modulate lung ventilation and adjust respiratory airflow, which depends on the upper airway patency and ventilatory musculature. Anesthetics are widely used in clinical practice worldwide. In addition to clinically necessary pharmacological effects, respiratory depression is a critical side effect induced by most general anesthetics. Therefore, understanding how general anesthetics modulate the respiratory system is important for the development of safer general anesthetics. Currently used volatile anesthetics and most intravenous anesthetics induce inhibitory effects on respiratory outputs. Various general anesthetics produce differential effects on respiratory characteristics, including the respiratory rate, tidal volume, airway resistance, and ventilatory response. At the cellular and molecular levels, the mechanisms underlying anesthetic-induced breathing depression mainly include modulation of synaptic transmission of ligand-gated ionotropic receptors (e.g., γ-aminobutyric acid, N-methyl-D-aspartate, and nicotinic acetylcholine receptors) and ion channels (e.g., voltage-gated sodium, calcium, and potassium channels, two-pore domain potassium channels, and sodium leak channels), which affect neuronal firing in brainstem respiratory and peripheral chemoreceptor areas. The present review comprehensively summarizes the modulation of the respiratory system by clinically used general anesthetics, including the effects at the molecular, cellular, anatomic, and behavioral levels. Specifically, analgesics, such as opioids, which cause respiratory depression and the
Keywords: respiratory rhythm